cis-regulatory elements involved in ultraviolet light regulation and plant defense. - Wingender, R (1990)
An elicitor-regulated transient expression system was established in soybean protoplasts that allowed the identification of cis-regulatory elements involved in plant defense. The 5' region of an ultraviolet (UV) light-inducible and elicitor-inducible chs gene (chs1) of soybean was subjected to deletion analysis with the help of chimeric chs-nptII/gus gene constructs. This analysis delimited the sequences necessary for elicitor inducibility to -175 and -134 of the chs1 promoter. The same soybean sequences were able to direct elicitor inducibility in parsley protoplasts, suggesting a conserved function of cis-acting elements involved in plant defense. In addition, this region of the soybean promoter also promotes UV light inducibility in parsley protoplasts. However, in contrast to the elicitor induction, correct regulation was not observed after UV light induction when sequences downstream of -75 were replaced by a heterologous minimal promoter. This result indicates that at least two cis-acting elements are involved in UV light induction.